Comparisons of Various Anthropometric Indices for Incident Hypertension in Military Young Adults: The CHIEF Cohort Study - Tsai, Kun-Zhe; Lin, Yen-Chen; Huang, Chen-Ming; Yang, Kai-Ti; Chen, Han-Hsing; Wang, Hui-Shang; Lin, Gen-Min (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
AimThe study aimed to compare the predictive capabilities of the traditional anthropometric indices with the novel anthropometric indices for incident hypertension.BackgroundSome novel anthropometric indices, e.g., the Body Roundness Index (BRI) and A Body Shape Index (ABSI) have been associated with prevalent hypertension. There are a few cohort studies that have examined the association of the novel anthropometric indices with new-onset hypertension in young adults.MethodsThis study included 2,448 military male and female young adults, aged 18-39 years, free of hypertension at baseline in Taiwan; they were followed for incidence of hypertension from 2014 till the end of 2020. Blood Pressure (BP) in mmHg was measured twice and averaged to verify hypertension, which was defined as systolic BP ≥130 and/or diastolic BP ≥80 or on antihypertensive medication therapy in each annual health examination. Anthropometric indices included the Body Mass Index (BMI) defined as the weight (kg)/height squared (m2), Waist Girth (WC) in cm, the Waist-to-height Ratio (WHtR), the BRI defined as 364.2 - 365.5 × 1 – [(WC/2π)/(0.5 × height)]20.5, as well as ABSI defined as WC/(BMI2/3 × height1/2). Multiple Cox regression analysis and Area Under the Curve (AUC) of the Receiver of Operating Characteristics (ROC) were utilized with adjustments for the baseline potential covariates to determine the association and compare the performance of various indices for incident hypertension.ResultsDuring a median follow-up period of 6.0 years, 920 new-onset hypertension cases (37.6%) developed. Higher BMI, WC, BRI (per each 1-unit increase) and WHtR (per each 0.1-unit increase) were associated with a greater risk of new-onset hypertension (Hazard Ratios (HRs) and 95% confidence intervals: 1.060 (1.035-1.085), 1.021 (1.011-1.030), and 1.178 (1.077-1.288), respectively), whereas there was no association between ABSI and new-onset hypertension. For the ROC, WC was observed with the greatest AUC for incident new-onset hypertension (0.661 (0.638-0.683)), followed by BMI (0.650 (0.628-0.673)), while the ABSI was found with the lowest AUC (0.544 (0.521-0.568)).ConclusionMost of the anthropometric indices were associated with a higher risk of new-onset hypertension among young adults, except for ABSI. In addition, this study has suggested the traditional indices, such as WC and BMI, to be superior to the latest ones, e.g., BRI and ABSI, for the prediction of new-onset hypertension.
Keywords: waist to height ratio